Proceedings of the Aristotelian Society 1992 - Aristotelian Society (Great Britain); Budd, Malcolm (. Aristotelian Society, 1900)
List of members in each volume
Includes Report of the executive committee for 1900/01-1914/15
Synoptic index: 1900-49. 1954. 1 v; 1950-59. 1961. 1 v.; 1960-69. 1975. 1 v
Keywords: Philosophy -- Societies, etc